FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ANEMIA PADA IBU HAMIL TRIMESTER III - Suyani (Stikes Muhammadiyah Klaten, 2019)
This study aims to determine the factors associated with the incidence of anemia in third trimester pregnant women at BPM Tri Rahayu Setyaningsih. This study used a quantitative design with a cross sectional study design. The sample in this study was taken with a total sampling technique of 59 respondents. The data used secondary data, by analyzing the cohort of pregnant women and classifying the factors associated with the incidence of anemia. Data analysis used Chi Square statistical test. The results showed that the incidence of anemia in pregnant women in the third trimester at BPM Tri Rahayu Setyaningsih was 26 people (44.1%). Based on the Chi Square statistical test with a significance level of 0.05, it was found that there was a relationship between pregnancy distance and the incidence of anemia with a p-value. value 0.001, there is a relationship between age and the incidence of anemia with a p-value of 0.018, there is a relationship between the frequency of ANC and the incidence of anemia with a p-value of 0.035, there is a relationship between parity and the incidence of anemia with a p-value of 0.001 and there is a relationship between status nutrition and the incidence of anemia with a p-value of 0.001. The results of logistic regression analysis showed that the factor that most influenced the incidence of anemia in pregnant women was the pregnancy distance OR value of 10.4 (95% CI: 2.35-7.21) which means that the risk pregnancy distance is <2 years and > 10 years are more likely to experience anemia 10.4 times compared to pregnant women whose pregnancy is not at risk (2-10 years).